PENGARUH MARKETING MIX , KUALITAS PELAYANAN DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS PELANGGAN DI BENGKEL NISSAN PALEMBANG - Muliyawan, Muliyawan; Fifian Permata Sari; Munajat, Munajat (Media Bina Ilmiah, 2025)
This study aims to analyze the effect of marketing mix, service quality and customer satisfaction on customer loyalty. The method used in this study is quantitative analysis method. The sampling method used in the study is non-probability sampling or random chance. This method is a method with sampling that does not provide equal opportunities to members of the population, and its determination is not random. In this study, all consumers who come to the Nissan workshop to service their cars are taken as samples. The number of samples taken for the study was 120 consumers. The data processing method uses multiple regression and multicollinearity test. Multicollinearity testing is used to determine whether or not there is a linear relationship between independent variables in the regression model. The prerequisite that must be met in the regression model is the absence of multicollinearity. Multicollinearity testing is carried out by looking at the value of Tolerance and Variance Inflation Factor (VIF). Data does not experience multicollinearity if the VIF value is below 5. Based on the results of the study, the influence of Marketing Mix, service quality and customer satisfaction on customer loyalty simultaneously has a positive and significant effect on customer loyalty at the Nissan Palembang Workshop and partially has a positive and significant effect on customer loyalty at the Nissan Palembang Workshop.